(untitled) (Journal of Shaheed Suhrawardy Medical College, 2019)
Background: In obstetric management fetal weight estimation is an important consideration when planning the mode of delivery in our day to day practice. In Bangladesh low birth weight is a major public health problem & incidence is 38% - 58%. Neonatal mortality and morbidity also yet high. So accurate antenatal estimation of fetal weight is a good way to detect macrosomia or small for date baby. Thus to improve the pregnancy outcome and neonatal outcome decreasing various chance of neonatal mortality and morbidity antenatal fetal weight prediction is an invaluable parameter in some situation where to identify the at risk pregnancy for low birth weight become necessary. Reliable method for prenatal estimation of fetal weight two modalities have got popularity - Clinical estimation and another one is ultrasonic estimation. This study was designed to determine the accuracy of clinical versus ultrasound estimated fetal weight detecting the discrepancy with actual birth weight at third trimester. So that we can verify more reliable and accurate method. Objectives: To find out more accurate and reliable modality of fetal weight estimation in antenatal period during obstetric management planning. To compare clinical versus ultrasound estimated fetal weight & to determine discrepancy of both variable with actual birth weight. Method: This prospective, cross sectional analytical study was carried out in Dhaka Medical College Hospital from January 2006 to December 2006. By purposive sampling 100 pregnant women fulfilling inclusion criteria were included in my study in third trimester (29wks-40wks). In clinical weight estimation procedure SFH (Symphysio Fundal Height) was measured in centimeter. On pervaginal finding whether vertex below or above the ischial spine was determined. By Johnson’s formula fetal weight in grams was estimated. Then by ultrasound scan different biometric measurements were taken and finally by Hadlock’s formula fetal weight was estimated. Eventually actual birth weight was taken after birth by Globe Brand weighing machine. Accuracy of both modalities were compared and which one was more reliable predictor was determined by statistical analysis. Results: After data collection were analyzed by computer based software (SPSS). There was gradual and positive relationship between symphysiofundal height and estimated birth weight. Discrepancy between clinical and actual birth weight at third trimester was statistically significant – Paired Student’s ‘t’ test was done where p value was <0.001. Whereas discrepancy between sonographically estimated fetal weight with actual birth weight was not statistically significant (by paired ‘t’ test where p value was >0.05). That implies discrepancy between ultrasound estimated fetal weight and actual birth weight was significantly less than that of clinically estimated fetal weight. 14% clinically and 46% sonographically estimated fetal weight were observed within £ 5% of actual birth weight. 31% clinical and 42% sonographically estimates observed within 6% to 10% of actual birth weight and 55% clinical and 12% sonographically estimate were >10% of actual birth weight. That is about 88% sonographical versus 45% clinical estimates were within 10% of actual birth weight. Conclusion: There is no doubt about importance of fetal weight in many obstetric situations. Clinical decisions at times depends on fetal weight. Whether to use oxytocin, to use forceps or vacuum for delivery or extend of trial or ended by Caesarian section immediately or no scope of trial to be largely depend on fetal size and weight. So more accurate modality for antenatal fetal weight estimation has paramount importance. In my study sonographically estimated weight have more accuracy than that of clinical estimate in predicting actual birth weight. Sonographically estimated fetal weight is more reliable, accurate and reproducible rather than other modality. J Shaheed Suhrawardy Med Coll, June 2019, Vol.11(1); 32-38